Prevalence of American Foulbrood and Paenibacillus Larvae Genotypes in Bulgaria - Nikolina V. RUSENOVA; Parvan R. PARVANOV (İstanbul Üniversitesi Veteriner Fakültesi Dergisi, 2016)
This study aimed to analyse the prevalence of American foulbrood and Paenibacillus larvae genotypes in Bulgaria. For this purpose, data concerning American foulbrood outbreaks were used. Also, available data on the number of destroyed bee families covering a twenty-five-year period (1989 - 2013) was collected from the register of Bulgarian Food Safety Agency. In addition, Paenibacillus larvae genotypes in 15 apiaries were established by rep - PCR with BOXA1R and MBOREP1 primers. Results showed broad incidence of the disease, particularly at the beginning of the analysed period, with a tendency to reduction of affected apiaries and bee families at the end of the period. A statistically significant prevalence of American foulbrood in South Bulgaria compared to the northern regions was observed. Genotyping of Paenibacillus larvae revealed two genotypes: ab and AB, with the preponderance of the more virulent AB in South Bulgaria. The obtained results showed the need for conducting regular mandatory screening of bee colonies for early diagnostics of the disease and the implementation of relevant measures for American foulbrood prevention and control.